2022
DOI: 10.3389/fcvm.2022.869501
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Effects of High-Intensity Interval Training vs. Moderate-Intensity Continuous Training on Left Ventricular Remodeling in Patients Early After ST-Segment Elevation Myocardial Infarction—The HIIT-EARLY Randomized Controlled Trial

Abstract: AimDue to insufficient evidence on the safety and effectiveness of high-intensity interval training (HIIT) in patients early after ST-segment elevation myocardial infarction (STEMI), we aimed to compare short- and long-term effects of randomized HIIT or moderate-intensity continuous training (MICT) on markers of left ventricular (LV) remodeling in STEMI patients receiving optimal guideline-directed medical therapy (GDMT).Materials and MethodsPatients after STEMI (<4 weeks) enrolled in a 12-week cardiac … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Advanced echocardiography could add key information in this setting with speckle-tracking-echocardiography-derived parameters. Currently, studies on the role of GLS [13][14][15][16][17][18][19] in evaluating the effect of exercise training on myocardial function have shown conflicting data. Moreover, the method is affected by various limitations, such as load dependence and lack of information on metabolic demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced echocardiography could add key information in this setting with speckle-tracking-echocardiography-derived parameters. Currently, studies on the role of GLS [13][14][15][16][17][18][19] in evaluating the effect of exercise training on myocardial function have shown conflicting data. Moreover, the method is affected by various limitations, such as load dependence and lack of information on metabolic demand.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies documented the positive effect of exercise training on GLS, specifically in patients with arterial hypertension [13,14], recent myocardial infarction [15], or recent ST-segment elevation myocardial infarction (STEMI) and LV ejection fraction > 45% [16]. However, other studies showed conflicting data on the improvement in GLS due to the training program [17,18], as well as in oncological patients undergoing cardio-oncology rehabilitation, suggesting the need for further investigations [19]. On the other hand, noninvasive MW has been poorly studied in the field of cardiac rehabilitation.…”
Section: Of 14mentioning
confidence: 99%
“…The bins range from the first quartile to the third quartile, a distance also known as the interquartile range (IQR). The boxplot notch represents the confidence interval around the median, which is usually based on the median ±1.58 * IQR/ √ n and gives a 95% confidence level (Eser et al 2022). If the boxplot notches for the CVs of the two groups do not overlap (Zhang et al 2022), then the CV distributions for all ECGs in that lead can be considered to be significantly different and statistically significant.…”
Section: C_twa Feature Statistical Analysismentioning
confidence: 99%
“…While HIIT improves echocardiographic parameters, myocardial work efficiency, and strain measures, 216 the HIIT-EARLY randomized controlled trial observed a long-term worsening of GLS in optimally-treated patients after acute STEMI, with no significant differences in cardiac RR compared to moderate-intensity continuous training. 217 Conversely, moderate-intensity exercise training yields substantial benefits, enhancing exercise capacity without fluctuations in LV end-diastolic diameter (LVEDD), as evidenced in a 3-month programme post-AMI. 218 219 Although LV volume regression was absent, moderate-intensity treadmill training post-MI after successful primary PCI improved LV systolic function, regional function, and exercise capacity.…”
Section: Post-ischaemic Reverse Remodelling and Cardiac Rehabilitationmentioning
confidence: 99%
“…However, the efficacy of high‐intensity interval training (HIIT) compared to moderate‐intensity continuous training remains debatable. While HIIT improves echocardiographic parameters, myocardial work efficiency, and strain measures, 216 the HIIT‐EARLY randomized controlled trial observed a long‐term worsening of GLS in optimally‐treated patients after acute STEMI, with no significant differences in cardiac RR compared to moderate‐intensity continuous training 217 . Conversely, moderate‐intensity exercise training yields substantial benefits, enhancing exercise capacity without fluctuations in LV end‐diastolic diameter (LVEDD), as evidenced in a 3‐month programme post‐AMI 218 .…”
Section: Interventions That Trigger Reverse Remodellingmentioning
confidence: 99%